Responsivity of the Striatal Dopamine System to Methylphenidate—A Within-Subject I-123-β-CIT-SPECT Study in Male Children and Adolescents With Attention-Deficit/Hyperactivity Disorder - Aster, Hans-Christoph; Romanos, Marcel; Walitza, Susanne; Gerlach, Manfred; Mühlberger, Andreas; Rizzo, Albert; Andreatta, Marta; Hasenauer, Natalie; Hartrampf, Philipp E.; Nerlich, Kai; Reiners, Christoph; Lorenz, Reinhard; et al. (Frontiers in Psychiatry, 2022)
Background: Methylphenidate (MPH) is the first-line pharmacological treatment of attention-deficit/hyperactivity disorder (ADHD). MPH binds to the dopamine (DA) transporter (DAT), which has high density in the striatum. Assessments of the striatal dopamine transporter by single positron emission computed tomography (SPECT) in childhood and adolescent patients are rare but can provide insight on how the effects of MPH affect DAT availability. The aim of our within-subject study was to investigate the effect of MPH on DAT availability and how responsivity to MPH in DAT availability is linked to clinical symptoms and cognitive functioning. Methods Thirteen adolescent male patients (9–16 years) with a diagnosis of ADHD according to the DSM-IV and long-term stimulant medication (for at least 6 months) with MPH were assessed twice within 7 days using SPECT after application of I-123-β-CIT to examine DAT binding potential (DAT BP). SPECT measures took place in an on- and off-MPH status balanced for order across participants. A virtual reality continuous performance test was performed at each time point. Further clinical symptoms were assessed for baseline off-MPH. Results On-MPH status was associated with a highly significant change (−29.9%) of striatal DAT BP as compared to off-MPH (t = −4.12, p = 0.002). A more pronounced change in striatal DAT BP was associated with higher off-MPH attentional and externalizing symptom ratings (Pearson r = 0.68, p = 0.01). Striatal DAT BP off-MPH, but not on-MPH, was associated with higher symptom ratings (Pearson r = 0.56, p = 0.04). Conclusion Our findings corroborate previous reports from mainly adult samples that MPH changes striatal DAT BP availability and suggest higher off-MPH DAT BP, likely reflecting low baseline DA levels, as a marker of symptom severity.